L’arbitrage en réassurance : la fin d’une idylle ? - Havens III, Charles W. (Assurances, 1992)
In order to avoid resorting to the courts when faced with litigation, insurers and reinsurers have favored arbitration services. Today, arbitration and reinsurance no longer live in harmony. Charles W. Havens III, Partner of LeBoeuf, Lamb, Leiby & MacRae, an American law firm, explains why with numerous examples.